2001
DOI: 10.2165/00003088-200140120-00002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Non-Nucleoside Reverse Transcriptase Inhibitors

Abstract: Non-nucleoside reverse transcriptase inhibitors (NNRTIs) are a diverse group of compounds that induce allosteric changes in the human immunodeficiency virus type 1 (HIV-1) reverse transcriptase, thus rendering the enzyme incapable of converting viral RNA to DNA. Unlike nucleoside analogue inhibitors of reverse transcriptase, NNRTIs do not require sequential phosphorylation to elicit antiretroviral activity. There are currently 3 approved NNRTIs: nevirapine, delavirdine and efavirenz. Although possessing a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
137
1
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(150 citation statements)
references
References 38 publications
8
137
1
4
Order By: Relevance
“…Our estimate of risk (27.57%) is similar to G. Kigen results (27.00%) [20] and our observation was same to the previous surveys from the Netherlands, the United States, and Kenya where potential CSDIs were reported in 14-41% patients [2][3][4][5]. We observed that, risk for CSDIs have affected about 30% of patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our estimate of risk (27.57%) is similar to G. Kigen results (27.00%) [20] and our observation was same to the previous surveys from the Netherlands, the United States, and Kenya where potential CSDIs were reported in 14-41% patients [2][3][4][5]. We observed that, risk for CSDIs have affected about 30% of patients.…”
Section: Discussionsupporting
confidence: 91%
“…The interactions mechanism is either inducers or inhibitors of CYP enzymes. Further, PIs are substrates and/or inhibitors of drug transporters such as P-glycoprotein which may result in pharmacokinetic drug interactions [2][3][4]. Indeed, managing drug-drug interactions is one of the major challenges in the optimization of HIV therapy [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter study ritonavir was dosed at 500 mg b.i.d., which, on a daily basis, is five times the dose used in the current study. Efavirenz is reported to have both inhibitory and inducing effects on CYP3A4 [25], and ritonavir depends mainly on CYP3A4 for its metabolism [9]. These data suggest that efavirenz coadministration may accelerate the metabolism of ritonavir administered at a low dose, which has also been reported previously [18].…”
Section: Discussionsupporting
confidence: 64%
“…In contrast to the NRTIs, the NNRTIs are not incorporated in the proviral DNA, but bind directly to the viral reverse transcriptase to block polymerase activity by causing a disruption of the enzyme catalytic site. [6] The NNRTIs are extensively metabolised by the liver via the CYP enzyme system. Besides substrates, NVP and EFV are both inducers of CYP3A4, whereas DLV acts as a potent inhibitor of CYP3A4.…”
Section: Non-nucleoside Reverse Transcriptase Inhibitorsmentioning
confidence: 99%
“…antidepressives or antibacterials) is used in addition to the antiretroviral regimen. Since both non-nucleoside reverse transcriptase inhibitors (NNRTIs) and PIs are extensively metabolised by the cytochrome P450 (CYP) system, [6,7] there is a considerable potential for pharmacokinetic interactions when these drugs are administered concomitantly with drugs metabolised via the same pathway. Awareness, recognition and management of drug interactions are important in the optimisation of pharmaceutical care to HIVinfected patients, helping to prevent adverse events and/or loss in efficacy of the drugs administered.…”
mentioning
confidence: 99%